Sonographic markers of fetal adiposity and risk of Cesarean delivery. (4th September 2019) - Hehir, M. P.; Burke, N.; Burke, G.; Turner, M. J.; Breathnach, F. M.; Mcauliffe, F. M.; Morrison, J. J.; Dornan, S.; Higgins, J.; Cotter, A.; Geary, M. P.; Mcparland, P.; et al.
ABSTRACT: Objective: Increased fetal size is associated with shoulder dystocia during labor and subsequent need for assisted delivery. We sought to investigate if increased fetal adiposity diagnosed sonographically in late pregnancy is associated with increased risk of operative delivery. Methods: This secondary analysis of the Genesis Study recruited 2392 nulliparous women with singleton pregnancy in cephalic presentation, in a prospective, multicenter study, to examine prenatal and intrapartum predictors of Cesarean delivery. Participants underwent ultrasound and clinical evaluation between 39 + 0 and 40 + 6 weeks' gestation. Data on fetal biometry were not revealed to patients or to their managing clinicians. A fetal adiposity composite of fetal thigh adiposity and fetal abdominal wall thickness was compiled for each infant in order to determine whether fetal adiposity > 90 th centile was associated with an increased risk of Cesarean or operative vaginal delivery. Results: After exclusions, data were available for 2330 patients. Patients with a fetal adiposity composite > 90 th centile had a higher maternal body mass index (BMI) (25 ± 5 kg/m 2 vs 24 ± 4 kg/m 2 ; P  = 0.005), birth weight (3872 ± 417 g vs 3585 ± 401 g; P  < 0.0001) and rate of induction of labor (47% (108/232) vs 40% (834/2098); P  = 0.048) than did those with an adiposity composite ≤ 90 th centile. Fetuses with adiposity composite > 90 th centile were more likely to require Cesarean delivery than were those with adiposity composite ≤ 90 th centile ( P  < 0.0001). After adjusting for birth weight, maternal BMI and need for induction of labor, fetal adiposity > 90 th centile remained a risk factor for Cesarean delivery ( P  < 0.0001). A fetal adiposity composite > 90 th centile was more predictive of the need for unplanned Cesarean delivery than was an estimated fetal weight > 90 th centile (odds ratio, 2.20 (95% CI, 1.65–2.94; P  < 0.001) vs 1.74 (95% CI, 1.29–2.35; P  < 0.001). Having an adiposity composite > 90 th centile was not associated with an increased likelihood of operative vaginal delivery when compared with having an adiposity composite ≤ 90 th centile ( P  = 0.37). Conclusions: Fetuses with increased adipose deposition are more likely to require Cesarean delivery than are those without increased adiposity. Consideration should, therefore, be given to adding fetal thigh adiposity and abdominal wall thickness to fetal sonographic assessment in late pregnancy. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.